Hypothesis: Cryptochromes and Brown Fat are Essential for Adaptation and Affect Mood and Mood-Related Behaviors - Partonen, Timo (Frontiers in Neurology, 2012)
Solar radiation and ambient temperature have acted as selective physical forces among populations and thereby guided species distributions in the globe. Circadian clocks are universal and evolve when subjected to selection, and their properties contribute to variations in fitness within specific environments. Concerning humans, as compared to the remaining, the “evening owls” have a greater deviation from the 24-hour cycle, are under a greater pressure to circadian desynchrony and more prone to a cluster of health hazards with the increased mortality. Because of their position in the hierarchy and repressive actions, cryptochromes are the key components of the feedback loops on which circadian clocks are built. Based on the evidence a new hypothesis is formulated in which brown adipocytes with their cryptochromes are responsive to a broad range of physical stimuli from the habitat and through their activity ensure adaptation of the individual. The over-activated brown adipose tissue with deficient cryptochromes might induce disrupted thermoregulation and circadian desynchrony, and thereby contribute to lowered mood and pronounced depressive behaviors.